2017
DOI: 10.1007/s00221-017-5063-8
|View full text |Cite
|
Sign up to set email alerts
|

Let me be your guide: physical guidance improves spatial learning for older adults with simulated low vision

Abstract: Monitoring one's safety during low vision navigation demands limited attentional resources which may impair spatial learning of the environment. In studies of younger adults, we have shown that these mobility monitoring demands can be alleviated, and spatial learning subsequently improved, via the presence of a physical guide during navigation. The present study extends work with younger adults to an older adult sample with simulated low vision. We test the effect of physical guidance on improving spatial lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 53 publications
2
14
0
Order By: Relevance
“…Our findings suggest that the reduced FOV may be more detrimental with complex paths or risky navigation contexts. In addition, our results supporting effects of limited attentional resources on spatial learning can be generalized beyond the specific FOV manipulation to other contexts where mobility monitoring demands are high, such as with older adults (Barhorst-Cates et al, 2017; Schellenbach, Lövdén, Verrel, Krüger, & Lindenberger, 2010) or other visually impoverished environments. Finally, we hope to be able to use the current findings identifying challenges due to path complexity to inform the development of assistive devices that could compensate for increasing attentional demands.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Our findings suggest that the reduced FOV may be more detrimental with complex paths or risky navigation contexts. In addition, our results supporting effects of limited attentional resources on spatial learning can be generalized beyond the specific FOV manipulation to other contexts where mobility monitoring demands are high, such as with older adults (Barhorst-Cates et al, 2017; Schellenbach, Lövdén, Verrel, Krüger, & Lindenberger, 2010) or other visually impoverished environments. Finally, we hope to be able to use the current findings identifying challenges due to path complexity to inform the development of assistive devices that could compensate for increasing attentional demands.…”
Section: Discussionsupporting
confidence: 67%
“…Prior work from our laboratory has shown that spatial learning during navigation is impaired with both simulated severely degraded acuity and contrast sensitivity (Rand, Creem-Regehr, & Thompson, 2015) and severely restricted peripheral FOV (Barhorst-Cates, Rand, & Creem-Regehr, 2016) in a real-world environment, and has attributed the deficit in learning partially to the attentional demands of monitoring to ensure safe mobility (Barhorst-Cates et al, 2016; Rand et al, 2015). Much of the prior work on low-vision spatial perception and navigation has used large, highly structured indoor hallways (Barhorst-Cates et al, 2016; Barhorst-Cates, Rand, & Creem-Regehr, 2017; Rand et al, 2015) or single-room environments (Fortenbaugh, Hicks, Hao, & Turano, 2007; Fortenbaugh, Hicks, & Turano, 2008; Legge, Gage, Baek, & Bochsler, 2016; Legge, Granquist, Baek, & Gage, 2016; Yamamoto & Philbeck, 2013). However, everyday navigation often occurs outside the context of straightforward hallways or rooms and it is unknown how low vision affects spatial learning in more irregular spatial contexts.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that being physically guided by an experimenter while walking with simulated low vision (wearing blur goggles) reduced attentional resource demands as revealed by improved spatial memory. This finding was replicated by the authors in an older adult population as well (Barhorst-Cates et al, 2017). Altogether, these studies support the hypothesis that postural control and spatial navigation share attentional resources, and therefore CMI in older adults should be considered and better characterized when studying older individuals' navigation difficulties.…”
Section: Introductionsupporting
confidence: 77%
“…The cognitive demands of motor tasks interacting with spatial learning have been observed in previous studies (Kerr et al, 1985;Lövdén et al, 2005;Taillade et al, 2013;Rand et al, 2015;Barhorst-Cates et al, 2017). Though methods differed, all these former studies revealed an improvement in spatial memory or wayfinding when motor task demands were reduced.…”
Section: Interaction Of Postural Control With Spatial Learningmentioning
confidence: 70%
“…This method of simulation is consistent with other recent studies involving participants without visual impairments. [42,43] During the OMI condition, a fixation circle with a diameter of 13° visual angle was centered in the keyboard area, and an EyeX eye tracker (Tobii, Danderyd, Sweden [44]) was used to ensure that participants kept their gaze within the circle. During pilot testing, a 13° circle was the smallest size that allowed some users to type successfully.…”
Section: Methodsmentioning
confidence: 99%